Penguatan Respons Darurat Masyarakat Pesisir Melalui Pelatihan Bantuan Hidup Dasar - Ramadan A, Rizqy; Halimatus S, Halimatus S; Erlina A, Cindy; Merinda O, Nabila; Oktavia H, Naura; Insani, Rizky; Najwa, Adzkia; Anwar H, Faisal; Hidayat, Faruq; Risqi Q, Muhammad; Prakoso, Denny Anggoro (Prosiding Seminar Nasional Program Pengabdian Masyarakat, 2025)
Sawahan Hamlet, located in Banaran Village, Galur District, Kulon Progo, is an area located in a coastal area with gentle and flat topography. However, this geographical condition also places the hamlet at high risk of emergencies, such as natural disasters, accidents, or medical emergencies that can happen anytime and affect anyone. Limited access to health services in the area, coupled with the long distance to the nearest medical facility, exacerbates the threat of death or complications due to slow treatment. In this context, Basic Life Support (BLS) training for Sawahan Hamlet youth is a strategic and potential solution to increase community responsiveness. The young generation, who have high mobility and response speed, are able to be the front line in saving lives before professional help arrives. The purpose of this community service is to improve the knowledge and skills of Karang Taruna youth in handling emergencies through BLS training. This community service activity includes counseling on emergency handling and BLS first aid training. BLS training successfully improved the knowledge and skills of adolescents in emergency management (significant increase, p<0.05, and average practice score 92.8), so it is necessary to strengthen this program to expand the scope of training and make it part of the health risk mitigation system in the region. Thus, collaboration between parties is needed to disseminate BLS to other adolescents and include it as a regular program at the village level, in order to maximize the role of the younger generation as the vanguard of emergency management.